2022
DOI: 10.1089/tmj.2022.0021
|View full text |Cite
|
Sign up to set email alerts
|

The First Year of Noninvasive Remote Telemonitoring in Chronic Heart Failure Is not Cost Saving but Improves Quality of Life: The Randomized Controlled CardioBBEAT Trial

Abstract: Introduction: Remote telemonitoring (RTM) for patients with chronic heart failure (HF) holds promise to improve prognosis and well-being beyond the standard of care (SoC). The CardioBBEAT trial assessed the health economic and clinical impact of an interactive bidirectional RTM system (Motiva ® ) versus SoC for patients with HF and a reduced ejection fraction (HFrEF), in Germany. Methods: This multicenter, randomized controlled trial enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Table 1 summarizes the general characteristics of the included studies. Of the 27 studies, 13 (48%) were conducted using a decision analytical model [ 31 - 35 , 40 , 47 - 51 ], 13 (48%) used trial-based data [ 36 - 39 , 41 - 46 , 54 - 57 ], and 1 (4%) used a combination of both [ 41 ]. The majority of the studies (25/27, 93%) were from HICs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the general characteristics of the included studies. Of the 27 studies, 13 (48%) were conducted using a decision analytical model [ 31 - 35 , 40 , 47 - 51 ], 13 (48%) used trial-based data [ 36 - 39 , 41 - 46 , 54 - 57 ], and 1 (4%) used a combination of both [ 41 ]. The majority of the studies (25/27, 93%) were from HICs.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies (25/27, 93%) were from HICs. Of the 27 studies, 6 (22%) were from the United States [ 34 , 43 , 44 , 51 - 53 ]; 3 (11%) each from the Netherlands [ 33 , 37 , 40 ] and the United Kingdom [ 32 , 35 , 50 ]; 2 (7%) each from Germany [ 36 , 38 ], Brazil [ 41 , 45 ], Canada [ 42 , 48 ], Italy [ 55 , 56 ], and Spain [ 46 , 49 ]; and 1 (4%) each from Australia [ 57 ], Poland [ 54 ], France [ 31 ], Hong Kong [ 47 ], and Denmark [ 39 ]. Of the 27 studies, 24 (89%) conducted a cost-utility analysis with cost and QALY as the outcome measures [ 31 - 35 , 37 - 40 , 42 - 51 , 54 , 56 , 57 ], 2 (7%) conducted a cost-effectiveness analysis (1/2, 50% with hospital readmission as the outcome measure [ 41 ] and 1/2, 50% with number of days alive and neither in hospital nor in inpatient care as the outcome measure [ 36 ]), and 1 (3%) conducted a cost-minimization analysis [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve ( 9 , 11 14 , 16 , 20 24 , 26 ) studies involving a total of 4,059 patients assessed all-cause mortality. Due to the high homogeneity of the included studies ( I 2 = 0%, P = 0.46), the fixed effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Eight ( 8 , 13 , 14 , 16 , 20 , 21 , 25 , 26 ) studies involving 2279 patients reported findings on all-cause hospitalization rate. Due to the high heterogeneity, the random effects model was used in this study ( I 2 = 67.5%, P = 0.00).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation